Gambaran Self-Efficacy Pada Dewasa Awal Yang Mengalami Quarter Life Crisis - Alzahrah Maharani; Andi Mifzal Fauzan; Nabila Alya Syam; Andi Nasrawati Hamid (CV. ULIL ALBAB CORP, 2024)
Individuals who do not prepare themselves well will experience a sense of worry and fear when they enter adulthood and if it starts to be felt, then the individual can be said to be experiencing a quarter life crisis. One of the abilities that individuals must have to be able to survive is high self-efficacy because self- efficacy has a big contribution to the crisis conditions experienced. This study aims to describe the quarter life crisis in early adulthood and the form of self- efficacy in early adults who experience a quarter life crisis. The subjects in this study were three early adults. This study uses a qualitative research method with a phenomenological approach. The results of the study show that individuals who experience quarter life crisis are often faced with difficult choices, experience pressure, and have negative feelings. Individuals who have high self-efficacy tend to have the ability to solve problems, set goals, and believe in their own abilities and be able to use problem-solving strategies, set realistic goals, and have confidence that they are able to overcome obstacles that arise.